The case for reintroducing universal child allowance in 21st century New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy at Massey University - Leigh, Gillian R (Massey University, 2006)
The purpose of this thesis is to contribute to contemporary debates on the most suitable family financial assistance policies for 21st century New Zealand. Based on documentary research, using books, articles, theses and official sources, this thesis presents a case in favour of reintroducing a universal child allowance within the mix of financial support to New Zealand children. The reason for a focus on this benefit is that it would arguably help meet a number of vitally important policy goals, while contributing to the wellbeing of families raising children. Current challenges for social policy in most OECD countries include low birth rates and projected long-term labour shortages. Policies to encourage higher labour force participation rates by mothers without further falls in fertility are recommended by the OECD and have already begun in countries such as New Zealand. In addition, the United Nations Millennium Goals include the eradication of poverty and the empowerment of women by 2015. One way to help New Zealand meet these goals would be to reintroduce a universal child allowance. This thesis argues that reintroducing a universal child allowance payable to the primary carer, commonly the mother, would be of assistance in reducing child and maternal poverty in New Zealand, including the hidden poverty that exists when aggregate household income is adequate but not fairly shared. Providing a reliable and regular income, would also contribute to the empowerment of women. It would remove the poverty traps that exist because of means-tested benefits, and which create disincentives to longer hours of employment. It would also reduce current financial difficulties that are causing couples to delay having children. This thesis outlines the New Zealand history of universal family benefit from its introduction until its abolition in 1991, and describes some of its effects and its popularity. The thesis examines the effectiveness of universal child benefits in countries such as Britain where they are still an integral part of the welfare system. It also looks in detail at a range of ways in which universal child allowance could help New Zealand meet some of the major policy challenges of the 21st century.
Keywords: New Zealand; Child support